The Relationship Between Anxiety Level And Shooting Accuracy - Hasmyati, Hasmyati; Mappanyukki, Andi Attsam (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This study aims to examine the relationship between the level of anxiety and shooting accuracy in Sinjai futsal athletes. The results showed that there was a significant relationship between the two variables. Anxiety has the potential to interfere with the player’s concentration and focus, which can affect shooting accuracy. Therefore, anxiety management is a key factor in improving the shooting accuracy ability of futsal athletes. The research method used was a correlational method involving 20 Sinjai futsal athletes as a sample. Data was collected through observation and futsal shooting tests and then analyzed using descriptive and inferential statistical methods. It was concluded that there was a significant correlation between the level of anxiety and the ability to shoot accuracy in Sinjai futsal athletes.